Al2O3:C optically stimulated luminescence dosimeters (OSLDs) for ultra-high dose rate proton dosimetry. (15th April 2021) - Christensen, Jeppe Brage; Togno, Michele; Nesteruk, Konrad Pawel; Psoroulas, Serena; Meer, David; Weber, Damien Charles; Lomax, Tony; Yukihara, Eduardo G; Safai, Sairos
Abstract: The response of Al2 O3 :C optically stimulated luminescence detectors (OSLDs) was investigated in a 250 MeV pencil proton beam. The OSLD response was mapped for a wide range of average dose rates up to 9000 Gy s −1, corresponding to a ∼150 kGy s −1 instantaneous dose rate in each pulse. Two setups for ultra-high dose rate (FLASH) experiments are presented, which enable OSLDs or biological samples to be irradiated in either water-filled vials or cylinders. The OSLDs were found to be dose rate independent for all dose rates, with an average deviation <1% relative to the nominal dose for average dose rates of (1–1000) Gy s −1 when irradiated in the two setups. A third setup for irradiations in a 9000 Gy s −1 pencil beam is presented, where OSLDs are distributed in a 3 × 4 grid. Calculations of the signal averaging of the beam over the OSLDs were in agreement with the measured response at 9000 Gy s −1 . Furthermore, a new method was presented to extract the beam spot size of narrow pencil beams, which is in agreement within a standard deviation with results derived from radiochromic films. The Al2 O3 :C OSLDs were found applicable to support radiobiological experiments in proton beams at ultra-high dose rates.